Associated factors to a high degree of disability due to tinnitus in the Otorhinolaryngology service’s patients of a Clinic in Lima - Santos, Mariah (2023)
The goal of this investigation was to determine the factors associated with a higher degree of disability due to tinnitus in patients of the otorhinolaryngology service in a clinic in Lima-Peru. The sample consisted of 100 patients who reported suffering from tinnitus, to whom the Tinnitus Handicap Inventory (THI) questionnaire was applied. For the comparative analysis, either the Chi-Square or the Kruskal-Wallis test was used. To determine the association between the study variables, Poisson regression models were used, with 95% confidence intervals. Of the participants, 94% exhibited some degree of disability due to tinnitus. For 40% of the patients the disability was found to be severe. For every subsequent year of age, the probability of suffering from severe disability due to tinnitus increases by 7%, while being hypertensive and having depression increased this probability by 8 and 4.8 times, respectively. In conclusion, age, hypertension and depression are factors associated with a higher degree of disability due to tinnitus.